Signet-ring cell aggregates simulating carcinoma in colon and gallbladder mucosa - Michal, M; Chlumska, A; Mukensnabl, P (Pathology, research and practice, 1998)
We describe three cases of benign signet-ring cell aggregates in the colon associated with pseudomembranous colitis, adenomatous polyp of the colon and ulcerated mucosa of the gallbladder excised for gallstones. In all cases, we found loose, benign signet-ring cell aggregates overlying the ulcerated mucosa surface, simulating signet ring-cell carcinoma. The most important sign of the benign signet-ring cell aggregates is that they are always confined to the surface of the mucosa of the intestine or gallbladder mucosa or crypts of the intestinal epithelium. In no case did we see an invasion of these cells into the lamina propria of the mucosa. In all cases, the benign signet-ring cell aggregates were immunohistochemically positive with antibodies to cytokeratins. The occurrence of benign signet-ring cell aggregates is a rare and very misleading diagnostic pitfall which must be differentiated from signet-ring cell carcinoma of the colon and gallbladder.
Keywords: diferenciální diagnóza; Keratins; imunohistochemie; pseudomembranózní enterokolitida; Middle Aged; mužské pohlaví; Intestinal Mucosa; Enterocolitis, Pseudomembranous; nádory tračníku; keratiny; Immunohistochemistry; ženské pohlaví; karcinom z prstenčitých buněk; Adenomatous Polyps; Humans; Gallbladder Neoplasms; Carcinoma, Signet Ring Cell; Colonic Neoplasms; lidé středního věku; střevní sliznice; nádory žlučníku; Diagnosis, Differential; adenomové polypy; Female; lidé; Male